2020
DOI: 10.1001/jamaoncol.2019.6496
|View full text |Cite
|
Sign up to set email alerts
|

HSD3B1 Genotype and Clinical Outcomes in Metastatic Castration-Sensitive Prostate Cancer

Abstract: The adrenal-restrictive HSD3B1(1245A) allele limits extragonadal dihydrotestosterone synthesis, whereas the adrenal-permissive HSD3B1(1245C) allele augments extragonadal dihydrotestosterone synthesis. Retrospective studies have suggested an association between the adrenal-permissive allele, the frequency of which is highest in white men, and early development of castration-resistant prostate cancer (CRPC).OBJECTIVE To examine the association between the adrenal-permissive HSD3B1(1245C) allele and early develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 31 publications
5
50
0
Order By: Relevance
“…Hearn et al have demonstrated this in their recent results using a population derived from the CHAARTED trial, and previous studies have alluded to this. 5 Current data support the idea of HSD3B1 as a predictive biomarker of progression on ADT therapy. The downside of this possible biomarker is that it is not applicable to all races.…”
supporting
confidence: 53%
See 3 more Smart Citations
“…Hearn et al have demonstrated this in their recent results using a population derived from the CHAARTED trial, and previous studies have alluded to this. 5 Current data support the idea of HSD3B1 as a predictive biomarker of progression on ADT therapy. The downside of this possible biomarker is that it is not applicable to all races.…”
supporting
confidence: 53%
“…4 Retrospective studies have suggested that the inheritance of the variant allele, HSD3B1(1245 C), is linked to decreased progression-free survival (PFS) and overall survival (OS) when compared to individuals with the wild-type allele, HSD3B1(1245A). 5 The Chemohormonal Therapy vs Androgen Ablation Randomized Trial for Extensive Disease in Prostate Cancer (CHAARTED) examined the clinical benefit of castration with or without docetaxel in men with metastatic prostate cancer. A 2020 study published in JAMA Oncology determined the HSD3B1 germline genotype in 475 white men who participated in the CHAARTED trial to explore clinical outcomes in relation to the determined genotype.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The HSD3B1(1245A) allele encodes for an adrenal restrictive enzyme that limits conversion from DHEA to downstream androgens, whereas the HSD3B1(1245C) allele encodes for an adrenal permissive enzyme that results in increased metabolic flux from DHEA to more potent androgens (16). Multiple studies from the United States, Japan, and Spain, now further confirmed in a phase 3 clinical trial, clearly show that men with advanced prostate cancer treated with castration who inherit the adrenal permissive 3β-HSD1 enzyme, which confers more rapid conversion from DHEA to potent androgens, have more rapid onset of androgendriven disease progression (17)(18)(19)(20)(21)(22). These studies establish that clear clinical phenotypes are associated with HSD3B1 genotypes that biochemically confer fast and slow metabolic flux to potent androgens.…”
Section: Significancementioning
confidence: 99%